An unusual presentation of sixth nerve palsy: neurobrucellosis - Mergen, Burak (GMS Ophthalmol Cases, 2019)
Abducens nerve palsy is generally seen in older patients with diabetes and hypertension. It is relatively rare in young and otherwise healthy patients. An extensive differential diagnosis is considered in patients younger than 50 years of age who develop a sixth nerve palsy. We report here a 25-year-old patient from Turkey who was admitted with sixth nerve palsy as a component of neurobrucellosis. She was referred to our clinic because she had double vision and restricted right eye abduction. During the ophthalmic examination, both pupils were round and reactive to light and accommodation. Extraocular movements were intact with the exception that the right eye was unable to abduct. Magnetic resonance imaging revealed no pathology. She also had a diagnosis of brucellosis and her abducens nerve palsy was a form of clinical manifestation of neurobrucellosis. We conclude that neurobrucellosis should be considered in patients with sixth cranial nerve palsy especially in areas where brucellosis is endemic.